PREDICTIVE EQUILIBRIUM SOLUTIONS OF THE SYSTEM OF EQUATIONS OF DEMAND AND SUPPLY OF PRODUCTS IN POORLY FORMALIZED PROCESSES - Abduhalil Abdugafarov; Barno Solieva; Nargiza Iminova; Kamoliddin Xudayberdiev (Galaxy International Interdisciplinary Research Journal, 2024)
Changes in the market prices of monopolists and other economic entities must be sufficiently justified, i.e. specific reasons for the increase in prices should be indicated, on what basis the increase in prices is expected. In the article a list of tasks to be solved jointly with the marketing service of the company - forecasting the equilibrium price of products, goods and services is proposed with fuzzy initial information.